IMPLEMENTASI KEBIJAKAN ZERO WSTE TO LANDFILL UNILEVER DALAM PENGELOLAAN LIMBAH PRODUK DI INDONESIA - Susilo, Annisa Aulia; Retnaningsih, Umi Oktyari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
Multinational companies in the Fast Moving Consumer Goods (FMCG) sector are a major contributor to plastic waste due to their high production and consumption. Meanwhile, the world is responding to environmental issues by encouraging the implementation of sustainability principles through the Sustainable Development Goals (SDGs) framework, particularly point 12 on Responsible Consumption and Production, which emphasizes responsible resource and waste management. Unilever, one of the FMCG companies, is addressing this issue through its internal Zero Waste to Landfill policy and several waste management programs. This study aims to analyze the implementation of this policy in Indonesia and assess its effectiveness from a Corporate Social Responsibility (CSR) perspective using a Green Thought approach. This study used a descriptive qualitative method with primary data in the form of interviews with Unilever Indonesia's Head of Sustainable Environment and 12 product users, as well as secondary data from reputable international and national scientific journals, sustainability reports, and news media. The research focused on the period 2018–2025. The research results show that policy implementation through the Unilever Sustainable Living Plan (USLP), Care for Area Surrounding (CFAS), and The Unilever Compass programs is the most effective. However, their effectiveness is still limited, at only 17%, due to the high volume of plastic waste, limited program reach, and low public awareness. These findings indicate a gap between company policies and public participation. The implications of the research indicate the need for increased packaging innovation and broader program socialization. Thus, existing policies are not yet fully optimal in addressing waste problems comprehensively.